Link Design and Legacy Amplifier Limitation in Flex-Grid Optical Networks - Djamel Amar; Nicolas Brochier; Esther Le Rouzic; Jean-Luc Auge; Catherine Lepers; Bernard Cousin; Mohamad Kanj (IEEE Photonics Journal)
Flex-grid technology is an effective means to improve the spectral efficiency of optical communication. For a given amplifier spectral bandwidth, it gives rise to the increase in the number of optical channels as it reduces channel spacing. Therefore, in order to reap full benefits from the flex-grid saved spectrum, further amplification power is required with respect to conventional fixed grid. This is a strong limitation if the legacy amplifiers cannot meet this new requirement due to their optical power limits. In this paper, we demonstrate that exploiting the link margins allows the support of this increase while maintaining in use legacy amplifiers.